THE IMPACT OF INFORMATION TECHNOLOGY ON STUDENT’S ACHIEVEMENT AT THE UNIVERSITY OF FLORES IN THE CONTEXT OF SOCIO-CULTURAL RESILIENCE - Mude, Anastasia; Sara, Kristina (International Journal of Educational Best Practices, 2020)
This research aims to know the impacts between moral behavior, interaction with the community, and the impact of technology on Education which is the achievement index in Flores University especially in the study program of Accountant, management, Development Economics, and Information System. This research used the survey research approach with 95 respondents of the research sample. The method of analyzing data in this research was the correlation of Pearson Product Moment. To test the relation of some variables that used SPSS. The results of this research were: (1) The variable impact of Information systems on education had a positive impact on the achievement variable. (2) The interaction variable with the community did not have any impacts or influences on the achievement variable. (3) The moral behavior variable did not impact the achievement variable. It means that the use of good and right information technology will increase the students learning achievements, meanwhile the interaction with the community, and the moral behavior as the complement to support the students' success in gaining the good achievements in the University of Flores.